2017
DOI: 10.5222/head.2017.093
|View full text |Cite
|
Sign up to set email alerts
|

An Important Problem for Patient Safety: Nursing Handover

Abstract: Sağlık hizmetlerinde bakım kalitesinin yükseltilmesi, hemşirelik bakımının dökümante edilmesi ve hasta bilgilerinin sağlık profesyonelleri arasında doğru aktarılması hususunda önemli bir yere sahip olan hasta teslimi, aynı zamanda hasta güvenliği hedeflerinden etkin iletişim sürdürülmesinde de öncelikli unsurlardan biridir. Hasta teslim sürecinde hasta güvenliğinin sağlanmasında en önemli kilit nokta; doğru, eksiksiz ve anlaşılır bilginin doğru zamanda ve doğru kişilerce verilmesidir. Modern sağlık bakım siste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(42 reference statements)
0
3
0
1
Order By: Relevance
“…Ancak sağlık çalışanlarının aşırı iş yükü, yoğunluğu ve bazen de duyarsızlığı nedeniyle hastaların devri sırasında bir takım iletişim hataları yaşanabilmektedir. Tıbbi hataların en önemli nedenlerinden biri olan iletişim hatalarının önlenmesi için standart iletişim tekniklerin kullanılması gerekmektedir (17,18,19,20).…”
Section: İletişim Güvenliğinin Sağlanmasıunclassified
“…Ancak sağlık çalışanlarının aşırı iş yükü, yoğunluğu ve bazen de duyarsızlığı nedeniyle hastaların devri sırasında bir takım iletişim hataları yaşanabilmektedir. Tıbbi hataların en önemli nedenlerinden biri olan iletişim hatalarının önlenmesi için standart iletişim tekniklerin kullanılması gerekmektedir (17,18,19,20).…”
Section: İletişim Güvenliğinin Sağlanmasıunclassified
“…In addition, it was found that careful and accurate handover increased the quality of the information conveyed and the reliability of the treatment [8]. The most important point in the patient handover process is that accurate, complete and understandable information is given by the right people at the right time [9]. During patient handover, emergency nurses should report the patient's name and surname, the name and surname of the doctor carrying out admission, application complaints, planned treatments, tests performed, tests ongoing and to be performed, patient's diagnosis, vital signs, patient's allergies, intravenous fluid therapies, level of consciousness, and invasive procedures in the oral and written reports [9].…”
Section: Introductionmentioning
confidence: 99%
“…The most important point in the patient handover process is that accurate, complete and understandable information is given by the right people at the right time [9]. During patient handover, emergency nurses should report the patient's name and surname, the name and surname of the doctor carrying out admission, application complaints, planned treatments, tests performed, tests ongoing and to be performed, patient's diagnosis, vital signs, patient's allergies, intravenous fluid therapies, level of consciousness, and invasive procedures in the oral and written reports [9]. Tortosa-Alted et al (2021) reported that emergency care nurses generally tended to perform the handover orally instead of through a written handover report due to the chaotic and critical environment of the emergency room, and, consequently, this may lead to suspicions regarding patient safety [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation